The handbook of education and human development : new models of learning, teaching, and schooling (Cambridge, MA : Blackwell, 1996)
Setting the stage: how theories of human development relate to education. Biological and cultural foundations of pedagogy. Schooling minds.
Keywords: Education; Cognition; Child development; Learning, Psychology of; Cognition in children; Educational anthropology